Pulmonary embolism in patients with COVID-19 pneumonia: When we have to search for it?. Issue 206 (October 2021) - Filippi, L.; Sartori, M.; Facci, M.; Trentin, M.; Armani, A.; Guadagnin, M.L.; Prandoni, P.
Abstract: Background: COVID-19 is still a global challenge in regard for management and therapy. Pulmonary embolism (PE) seems to have a higher prevalence in COVID-19 instead of non-COVID patients. Clinical and laboratory parameters related with PE are still unknown. Methods: We conducted a retrospective unicentre study in Alto Vicentino Hospital between March 1st, 2020, and January 31st, 2021 in patients admitted for COVID-19 tested with a RT-PCR nasal swab. Data about patients studied with computed tomography pulmonary angiogram (CTPA) because of PE suspicion were collected, as their clinical and laboratory parameters too. Results: 2621 patients were admitted for COVID-19 in Alto Vicentino Hospital between March 1st, 2020, and January 31st, 2021 and in 267 of them a CTPA was performed finding 50 PE (18.7%). Only non-Caucasian race (OR = 5.44; 95% CI 1.22–24.35; p = 0.027) and previous VTE (OR = 5.3; 95% CI 1.09–26.17; p = 0.039) were found to be independently associated with PE. Conclusion: PE is a frequent complication of COVID-19 and clinician need high degree of suspicion because clinical and laboratoristic parameters cannot drive diagnosis. Highlights: This study tries to find a correlation between COVID-19 and pulmonary embolism. COVID-19 infection appears to be most correlated with thromboembolic events. Unfortunately, clinical and laboratoristic parameters cannot drive diagnosis of pulmonary embolism in COVID-19 patients.